Multiscale numerical simulation of the forming process of biaxial braids during thermoplastic braid-trusion: Predicting 3D and internal geometry and fiber orientation distribution. (November 2021) - Ghaedsharaf, Mohammad; Brunel, Jean-Evrard; Laberge Lebel, Louis
Graphical abstract: Highlights: The model predicts macroscopic braid architecture changes during pultrusion with an average accuracy of over 99%. Mesoscopic morphology and high local fiber volume fraction of a thermoplastic braid-truded rod is predicted. Local fiber orientation distributions vary along the braid radius; conversely, they are uniformly distributed along the braid pitch. There are significant differences between the local fiber orientation and the nominal braid angle. Abstract: Thermoplastic braid-trusion is a composite manufacturing process that combines braiding and pultrusion of hybrid yarns containing reinforcement and polymer fibers. During pultrusion, the melting of the polymer fibers leads to complex morphological changes at the macro, meso and micro scales. We introduce here a multiscale numerical simulation methodology to model this process. In this methodology, braided yarns are modeled as bundles of virtual discrete fibers using chains of truss elements. A thermoplastic composite braided rod was pultruded according to the simulated braid-trusion. During braid-trusion, it was observed that the braid architecture was significantly modified, which was reliably predicted by the model through macroscopic measurements of 7.6% pitch elongation, 44.0% diameter reduction, and 45.0% nominal angle reorientation. The model also predicts yarns' cross-section area having high local fiber volume fraction of about 60% due to yarn compaction during pultrusion. These predictions of mesoscopic morphology and internal geometry are quantitatively validated using X-ray micro-computed tomography (CT) scans of the braid-truded rod. Three local fiber orientation distributions of the in-plane, out-of-plane, and with respect to the longitudinal braid axis are extracted using micro-scale analysis of virtual fibers. We found that a significant amount of fibers are oriented around specific radii ranging from 30–70% and 60–100% of the outer radius before and after pultrusion, respectively. By contrast, the local fiber orientation is uniformly distributed along the pitch length. The microscale model also shows considerable discrepancies between local and nominal braid angles.